PERAN MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DI DESA GUMIRIH KECAMATAN SINGOJURUH KABUPATEN BANYUWANGI - Zaki Al Mubarok; Ellyana Ilsan Eka Putri (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2022)
This study aims to know how community participation in the development planning meeting in the village Gumirih subdistrict singojuruh. This study use field research and data collection in observation, interviews and documentation. Results of this study is the participation village Gumirih in the year 2019 is low. In addition discovered that the community in the partsipasi congress in 2019 step 2 therapy. Step it shows nonpartisipasi level designed by several parties to replace net enrollment.Where in the implementation of development programs village communities passive bersiikap just wait intruksi of the village officials so is top-down.